2006
DOI: 10.1080/17453670610046370
|View full text |Cite
|
Sign up to set email alerts
|

The olecranon sled—a new device for fixation of fractures of the olecranon: A mechanical comparison of two fixation methods in cadaver elbows

Abstract: Background Tension band wiring is the most common surgical procedure for fixation of fractures of the olecranon, but symptomatic hardware prominence and migration of K-wires can cause a high re-operation rate. The olecranon sled has been designed to minimize some of these problems.Material and methods Simulated olecranon fractures were created in 6 matched pairs of cadaver arms. Each pair was fixed with tension band wiring used on the one arm and the olecranon sled being used on the other. Mechanical testing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The advantages of low prominence and secure fixation of the sled may play an important role in reducing the rate of symptomatic metalwork removal [ 15 ]. Moreover, it can provide good clinical outcomes for olecranon fractures [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of low prominence and secure fixation of the sled may play an important role in reducing the rate of symptomatic metalwork removal [ 15 ]. Moreover, it can provide good clinical outcomes for olecranon fractures [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7 In this cadaveric study, simulated transverse olecranon fractures were fixed with either the olecranon sled or bicortical K-wires and tension band wiring. After application of cyclic loading of the biceps and triceps to the construct, there was no statistically significant difference in fracture displacement between the 2 fixation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical testing has shown that the olecranon sled performs similarly to a tension band construct in cadaveric models of olecranon fracture. 7 The purpose of this study is to evaluate our technique in using the olecranon sled in patients to repair olecranon osteotomies for exposure of intra-articular distal humerus fractures and to evaluate early outcomes and complications.…”
Section: Historical Perspectivementioning
confidence: 99%
“…To our knowledge, only 1 previous biomechanical study has compared the continuous loop construct with the traditional K-wire and tension band technique, finding no difference in osteotomy displacement. 5 However, the study did not compare intramedullary screw with tension band fixation or comment on hardware prominence. 5 Limited clinical data are available on the use of the Olecranon Sled.…”
mentioning
confidence: 99%
“…5 However, the study did not compare intramedullary screw with tension band fixation or comment on hardware prominence. 5 Limited clinical data are available on the use of the Olecranon Sled. 9,13 Iorio et al 9 reported on 14 patients, with 1 requiring hardware removal.…”
mentioning
confidence: 99%